Research on Anti-Jamming Algorithm Based on Beidou Satellite Navigation System - Lv, Cui Gai; Liu, Yu Hao; Zheng, Xiao Zhe (Applied Mechanics and Materials, 2013)
According to the four array elements of Beidou satellite navigation model as the research object, put forward a kind of Compass satellite navigation signal model construction method, and using Matlab software to build the satellite navigation signal system model . Based on the power inversion principle, try to use the recursive least squares (RLS) algorithm for getting the power inversion Optimum weights, compared and evaluated in terms of this performance. The results show that the power inversion based on RLS algorithm can make the antenna array in the direction of interference to automatically generate nulling .And compared with LMS power inversion array algorithm, RLS algorithm in interference can form deeper nulling. The disadvantage is computationally intensive.